ZIKV – CDB: A Collaborative Database to Guide Research Linking SncRNAs and ZIKA Virus Disease Symptoms - Pylro, Victor Satler; Oliveira, Francislon Silva; Morais, Daniel Kumazawa; Cuadros-Orellana, Sara; Pais, Fabiano Sviatopolk-Mirsky; Medeiros, Julliane Dutra; Geraldo, Juliana Assis; Gilbert, Jack; Volpini, Angela Cristina; Fernandes, Gabriel Rocha (PLOS Neglected Tropical Diseases, 2016)
Author Summary The potential interaction between ZIKA Virus (ZIKV) infection and infant brain defects still has no explanatory mechanism. The mechanism of action for several other viruses have been described, and are often related to the control or production of sncRNA (small noncoding RNA) molecules, which regulate the expression of several human genes. Based on this knowledge, we have predicted miRNAs (a kind of sncRNA) encoded by ZIKV genomes, and identified human miRNAs that may be able to interact with human genes related to microcephaly. To help support further investigation, we have created a searchable database for ZIKV miRNAs that may mimic human molecules and possibly interfere with the human gene expression; or to search for human sncRNA molecules that could be recruited by the ZIKV genome, and influence function. This database could aid investigators in elucidating the role played by sncRNAs in human ZIKV infection, and be used to identify novel therapeutic targets.